Pregnancy, alcohol intake, and intimate partner violence among men and women attending drinking establishments in a Cape Town, South Africa township. - Eaton, Lisa A; Kalichman, Seth C; Sikkema, Kathleen J; Skinner, Donald; Watt, Melissa H; Pieterse, Desiree; Pitpitan, Eileen V (Journal of community health, 2012)
The highest rates of fetal alcohol syndrome worldwide can be found in South Africa. Particularly in impoverished townships in the Western Cape, pregnant women live in environments where alcohol intake during pregnancy has become normalized and interpersonal violence (IPV) is reported at high rates. For the current study we sought to examine how pregnancy, for both men and women, is related to alcohol use behaviors and IPV. We surveyed 2,120 men and women attending drinking establishments in a township located in the Western Cape of South Africa. Among women 13.3% reported being pregnant, and among men 12.0% reported their partner pregnant. For pregnant women, 61% reported attending the bar that evening to drink alcohol and 26% reported both alcohol use and currently experiencing IPV. Daily or almost daily binge drinking was reported twice as often among pregnant women than non-pregnant women (8.4% vs. 4.2%). Men with pregnant partners reported the highest rates of hitting sex partners, forcing a partner to have sex, and being forced to have sex. High rates of alcohol frequency, consumption, binge drinking, consumption and binge drinking were reported across the entire sample. In general, experiencing and perpetrating IPV were associated with alcohol use among all participants except for men with pregnant partners. Alcohol use among pregnant women attending shebeens is alarmingly high. Moreover, alcohol use appears to be an important factor in understanding the relationship between IPV and pregnancy. Intensive, targeted, and effective interventions for both men and women are urgently needed to address high rates of drinking alcohol among pregnant women who attend drinking establishments.
Keywords: Adult; Alcohol Drinking; Cross-Sectional Studies; Ethanol; Female; Humans; Male; Pregnancy; Pregnant Women; Sex Offenses; Social Behavior; South Africa; Spouse Abuse